A lidar based national model of hedgerows and other woody linear features in rural England - Richard K. Broughton; Rich J. Burkmar; Morag E. McCracken; Nadine Mitschunas; Lisa R. Norton; Denise W. Pallett; Justine Patton; John W. Redhead; Jo T. Staley; Claire M. Wood; Richard F. Pywell (Journal of Environmental Management, 2025)

ECOBRIDGE: An expert system for spatial downscaling of land use/land cover change scenario outputs - Josep Serra Gallego; Hollie Blaydes; Emma Gardner; Richard F. Pywell; J. Duncan Whyatt; John W. Redhead (Environmental Modelling & Software, 2025)

Practical methods for the control of tor-grass (Brachypodium pinnatum s.l.) and the restoration of calcareous grassland - Lucy E. Ridding; John W. Redhead; Emily V. Upcott; Lucy Hulmes; Sarah Hulmes; Nadine Mitschunas; Katherine Howell; Jenny Christelow; Alexander R. Wickenden; Mike Fussell; James Plunkett; Richard F. Pywell (Journal for Nature Conservation, 2024)

Mapping the ratio of agricultural inputs to yields reveals areas with potentially less sustainable farming - James M. Bullock; Susan G. Jarvis; William N.W. Fincham; Hannah Risser; Carolin Schultz; David J. Spurgeon; John W. Redhead; Jonathan Storkey; Richard F. Pywell (Science of The Total Environment, 2024)

The potential to increase grassland soil C stocks by extending reseeding intervals is dependent on soil texture and depth - Dafydd M.O. Elias; Kelly E. Mason; Katherine Howell; Nadine Mitschunas; Lucy Hulmes; Sarah Hulmes; Inma Lebron; Richard F. Pywell; Niall P. McNamara (Journal of Environmental Management, 2023)

A new approach to characterising and predicting crop rotations using national-scale annual crop maps - Emily V. Upcott; Peter A. Henrys; John W. Redhead; Susan G. Jarvis; Richard F. Pywell (Science of The Total Environment, 2023)

Long-term change in calcareous grassland vegetation and drivers over three time periods between 1970 and 2016 - Lucy E. Ridding; James M. Bullock; Oliver L. Pescott; Peter Hawes; Robin Walls; M. Glória Pereira; Sarah A. Thacker; Patrick O. Keenan; Ulrike Dragosits; Richard F. Pywell (Plant Ecology, 2020)
Analysis of long-term vegetation change is limited. Furthermore most studies evaluating change only examine two snapshots in time, which makes it difficult to define rates of change and accurately assess potential drivers. To assess long-term change in calcareous grassland over multiple time periods, we re-surveyed a transect study undertaken at Parsonage Down National Nature Reserve, Wiltshire, southern England in 1970 and 1990 by T. Wells. We examined differences in soil properties and species traits in each of the survey years to understand potential drivers of vegetation change, including nitrogen deposition and grazing management. There was a clear shift in species composition, combined with significant declines in species richness and diversity between 1970 and 2016, with the greater rate of change occurring between 1990 and 2016. A significant increase in soil total nitrogen was found, which was significantly associated with the decline in species diversity between 1970 and 1990. Significant changes in community-weighted mean traits were identified for plant height (increasing), specific leaf area (decreasing), grazing tolerance (decreasing) and Ellenberg N (decreasing) between 1970 and 2016. By using survey data from multiple time periods, we suggest that N deposition may have contributed towards community changes between 1970 and 1990, as indicated by the change in soil properties and the associated decline in species diversity. Vegetation change between 1990 and 2016 is likely to be largely attributable to a decline in grazing pressure, indicated by the increase in taller species and a decrease in grazing tolerance.

Potential landscape‐scale pollinator networks across Great Britain: structure, stability and influence of agricultural land cover - John W. Redhead; Ben A. Woodcock; Michael J.O. Pocock; Richard F. Pywell; Adam J. Vanbergen; Tom H. Oliver (Ecology Letters, 2018)
Understanding spatial variation in the structure and stability of plant–pollinator networks, and their relationship with anthropogenic drivers, is key for maintaining pollination services and mitigating declines. Constructing sufficient networks to examine patterns over large spatial scales remains challenging. Using biological records (citizen science), we constructed potential plant–pollinator networks at 10 km resolution across Great Britain, comprising all potential interactions inferred from recorded floral visitation and species co‐occurrence. We calculated network metrics (species richness, connectance, pollinator and plant generality) and adapted existing methods to assess robustness to sequences of simulated plant extinctions across multiple networks. We found positive relationships between agricultural land cover and both pollinator generality and robustness to extinctions under several extinction scenarios. Increased robustness was attributable to changes in plant community composition (fewer extinction‐prone species) and network structure (increased pollinator generality). Thus, traits enabling persistence in highly agricultural landscapes can confer robustness to potential future perturbations on plant–pollinator networks.

Soil multifunctionality and drought resistance are determined by plant structural traits in restoring grassland - Ellen L. Fry; Joanna Savage; Amy L. Hall; Simon Oakley; W. J. Pritchard; Nicholas J. Ostle; Richard F. Pywell; James M. Bullock; Richard D. Bardgett (Ecology, 2018)
It is increasingly recognized that belowground responses to vegetation change are closely linked to plant functional traits. However, our understanding is limited concerning the relative importance of different plant traits for soil functions and of the mechanisms by which traits influence soil properties in the real world. Here we test the hypothesis that taller species, or those with complex rooting structures, are associated with high rates of nutrient and carbon (C) cycling in grassland. We further hypothesized that communities dominated by species with deeper roots may be more resilient to drought. These hypotheses were tested in a 3‐yr grassland restoration experiment on degraded ex‐arable land in southern England. We sowed three trait‐based plant functional groups, assembled using database derived values of plant traits, and their combinations into bare soil. This formed a range of plant trait syndromes onto which we superimposed a simulated drought 2 yr after initial establishment. We found strong evidence that community weighted mean ( CWM ) of plant height is negatively associated with soil nitrogen cycling and availability and soil multifunctionality. We propose that this was due to an exploitative resource capture strategy that was inappropriate in shallow chalk soils. Further, complexity of root architecture was positively related to soil multifunctionality throughout the season, with fine fibrous roots being associated with greater rates of nutrient cycling. Drought resistance of soil functions including ecosystem respiration, mineralization, and nitrification were positively related to functional divergence of rooting depth, indicating that, in shallow chalk soils, a range of water capture strategies is necessary to maintain functions. Finally, after 3 yr of the experiment, we did not detect any links between the plant traits and microbial communities, supporting the finding that traits based on plant structure and resource foraging capacity are the main variables driving soil function in the early years of grassland conversion. We suggest that screening recently restored grassland communities for potential soil multifunctionality and drought resilience may be possible based on rooting architecture and plant height. These results indicate that informed assembly of plant communities based on plant traits could aid in the restoration of functioning in degraded soil.

Functional diversity positively affects prey suppression by invertebrate predators: a meta‐analysis - Arran Greenop; Ben A. Woodcock; Andy Wilby; Samantha M. Cook; Richard F. Pywell (Ecology, 2018)
The use of pesticides within agricultural ecosystems has led to wide concern regarding negative effects on the environment. One possible alternative is the use of predators of pest species that naturally occur within agricultural ecosystems. However, the mechanistic basis for how species can be manipulated in order to maximize pest control remains unclear. We carried out a meta‐analysis of 51 studies that manipulated predator species richness in reference to suppression of herbivore prey to determine which components of predator diversity affect pest control. Overall, functional diversity ( FD ) based on predator's habitat domain, diet breadth and hunting strategy was ranked as the most important variable. Our analysis showed that increases in FD in polycultures led to greater prey suppression compared to both the mean of the component predator species, and the most effective predator species, in monocultures. Further analysis of individual traits indicated these effects are likely to be driven by broad niche differentiation and greater resource exploitation in functionally diverse predator communities. A decoupled measure of phylogenetic diversity, whereby the overlap in variation with FD was removed, was not found to be an important driver of prey suppression. Our results suggest that increasing FD in predatory invertebrates will help maximize pest control ecosystem services in agricultural ecosystems, with the potential to increase suppression above that of the most effective predator species.

Cereal density and N-fertiliser effects on the flora and biodiversity value of arable headlands - Markus Wagner; James M. Bullock; Lucy Hulmes; Sarah Hulmes; Richard F. Pywell (Biodiversity and Conservation, 2017)

The seed banks of English lowland calcareous grasslands along a restoration chronosequence - Kate C. Fagan; Richard F. Pywell; James M. Bullock; Rob H. Marrs (Plant Ecology, 2010)

Effects of vegetation structure and floristic diversity on detritivore, herbivore and predatory invertebrates within calcareous grasslands - Ben A. Woodcock; Richard F. Pywell (Biodiversity and Conservation, 2010)

Restoration of biodiversity enhances agricultural production - James M. Bullock; Richard F. Pywell; Mike J.W. Burke; Kevin J. Walker (Ecology Letters, 2001)
Restoration of ecological communities is important to counteract global losses in biodiversity. However, restoration on agricultural land is perceived as being costly because of losses in agricultural production. We suggest the reported positive relationship between diversity and productivity means biodiversity could be used to enhance agricultural production. We examined this in hay meadow restoration experiments at seven sites across southern Britain. At each site two seed mixes (“species‐poor” with 6–17 species and “species‐rich” with 25–41 species) were applied in a randomised block experiment. Hay yield was higher in the species‐rich treatment from the second year onward, by up to 60%. Comparing the two treatments in all sites, there was a simple linear relationship between the difference in species number and the amount of increase in hay production. Fodder quality was the same in both treatments. This suggests farmers can maximize high quality herbage production in re‐sown grasslands by maximizing biodiversity.